Implementing care for healthy ageing. Issue 2 (19th February 2022) - Cesari, Matteo; Sumi, Yuka; Han, Zee A; Perracini, Monica; Jang, Hyobum; Briggs, Andrew; Amuthavalli Thiyagarajan, Jotheeswaran; Sadana, Ritu; Banerjee, Anshu
Abstract : The WHO concept of Healthy Ageing (ie, the process of developing and maintaining the functional ability that enables well-being in older age) has initiated a global discussion about the need for shifting paradigms to reorient health and social services towards person-centred and coordinated models of care. In particular, the integration of health and social care services is critical to provide the basis for comprehensive information sharing and service delivery to support the evolution of the older person over time. The capability to monitor and respond to an older person's changing health and social care needs will enable prompt and personalised health and social care plans to be implemented. The implementation of an integrated care approach involves all the settings where persons age, but also requires a concerted action among micro (clinical), meso (service delivery) and macro (system) level. The community is of particular relevance given the primary objective of "ageing in place". However, from the perspective of the continuum of care and services acting synergistically, all health and social care settings (including long-term care facilities and hospitals) need to evolve and embrace an integrated way of operating to support functional ability in older people, while maximising resource and information sharing efficiencies. In this paper, we explain that government actions to promote well-being in older age should be built on a seamless continuum of care starting from the assessment of the older person's intrinsic capacity and functional ability with the final aim of providing care aligned with the individual's needs and priorities.